Perencanaan Make Up Water Tank Kapasitas 500 kl PLTGU Blok I, II, dan III PT PJB UP Gresik - Meryanalinda; Wardjito; Ahmad Setyawan (Wahana Teknik, 2020)
At the steam gas power plant (PLTGU) there are various kinds of equipment, namely common, Gas Turbine (GT), Steam Turbine (ST). In common, the main water system has a very important role. Where the water raw material will later be used as a cooling system & the main ingredient into steam (dry steam). This process starts from processing seawater into feed water that has a certain pH and conductivity, then it is processed in the water treatment plant (pH 8-9 and conductivity ≤ 1 µ/cm). To maintain the supply of the main ingredient of water, it is necessary to have a storage that functions to ensure the availability of make up water supply during normal unit operation. This research was conducted to find out in planning the make up water storage tank with a capacity of 500 kl at PLTGU Gresik Generation Unit. Dimension of make up water tank is 9,125 m high & 10 m diameter and using ASTM A36 material in accordance with API 650 standard. The calculation results are known that the thickness of the 1st shell plate is 7 mm, the 2nd shell plate is 6 mm, the 3rd shell plate is 5 mm, and the 4th shell plate is 5 mm. The thickness of the bottom plate and annular plate is 10 mm, with the results of these calculations it is recommended that a welding procedure be made according to the thickness of the shell plate. Keywords: API standard 650, Make up, Tank, Treatment, Water, Welding